Feedback and efficient behavior. - Sandro Casal; Nives DellaValle; Luigi Mittone; Ivan Soraperra (PLoS ONE, 2017)
Feedback is an effective tool for promoting efficient behavior: it enhances individuals' awareness of choice consequences in complex settings. Our study aims to isolate the mechanisms underlying the effects of feedback on achieving efficient behavior in a controlled environment. We design a laboratory experiment in which individuals are not aware of the consequences of different alternatives and, thus, cannot easily identify the efficient ones. We introduce feedback as a mechanism to enhance the awareness of consequences and to stimulate exploration and search for efficient alternatives. We assess the efficacy of three different types of intervention: provision of social information, manipulation of the frequency, and framing of feedback. We find that feedback is most effective when it is framed in terms of losses, that it reduces efficiency when it includes information about inefficient peers' behavior, and that a lower frequency of feedback does not disrupt efficiency. By quantifying the effect of different types of feedback, our study suggests useful insights for policymakers.